2021
DOI: 10.1002/eat.23600
|View full text |Cite
|
Sign up to set email alerts
|

Establishing consensus for labeling and defining the later stage of anorexia nervosa: A Delphi study

Abstract: Objective: Varied perspectives on the later stage of anorexia nervosa (AN) have left the field of eating disorders without a consistent label or definition for this subpopulation. As a result, diverse criteria when recruiting participants have led to incomparable results across research studies and a lack of guidance when assessing and treating patients in the clinical context. The aim of the current study was to develop consensus-based guidelines on the labeling and defining of the later stage of AN. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Usual stages of these processes include survey development based on literature review and core group input in which a core group develops potential consensus statements based on literature review and their own expertise, expert panel member recruitment, circulation of proposed statements to these larger groups of nominated experts, data collection and analyses for several rounds of survey votes and input, and ultimate consensus guideline development. [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usual stages of these processes include survey development based on literature review and core group input in which a core group develops potential consensus statements based on literature review and their own expertise, expert panel member recruitment, circulation of proposed statements to these larger groups of nominated experts, data collection and analyses for several rounds of survey votes and input, and ultimate consensus guideline development. [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 62.86% of statements reached consensus, representing an equal or higher amount of agreement amongst the expert panel compared to other Delphi studies in the field [ 38 , 45 ].…”
Section: Discussionmentioning
confidence: 89%
“…We also found that the child onset group had significantly higher rates of prior admissions to higher levels of care for their ED compared to both the adolescent and adult onset groups, a finding compatible with higher severity, chronicity and possibly poorer response to previous treatment. These results have implications for ‘severe and enduring’ AN and BN, although exact definitions, risk factors, and effective treatments remain elusive (Brewerton & Dennis, 2015; Broomfield et al., 2021; Kotilahti et al., 2020; Treasure et al., 2020; Westmoreland & Mehler, 2016; Wonderlich et al., 2020). Given that mean age of admission was not significantly different between the three groups, those with child onset ED have been living with an ED longer than those in the other two groups, although it is unknown to what extent remissions may have occurred in the interim.…”
Section: Discussionmentioning
confidence: 99%